Creator God, evolving world - Crysdale, Cynthia S. W., 1953- (UPCC book collections on Project MUSE., 2013)
In this book, the authors present a robust theology of God in light of supposed tensions between Christian belief and evolutionary science. Those who pit faith in an almighty and unchanging God over against a world in which chance is operative have it wrong on several accounts, they insist. This book clarifies a number of confused assumptions in an effort to redeem chance as an intelligible force interacting with stable patterns in nature.